Analisis Kebijakan Penetapan Wilayah Pertambangan Rakyat di Kabupaten Katingan Provinsi Kalimantan Tengah - Muhaimin Noor; Juliansyah Juliansyah (Pencerah Publik, 2015)
This research aims to explain and describe how policies for the establishment of people's mining areas in the Katingan district of central Kalimantan province, as well as any problems or constraints that become the policy of fixing People's mining areas in the Katingan district of central Kalimantan province. This research uses qualitative research, data sources consist of primary data sources (head of the field, head of the section, executive staff, and community). Techniques for collecting data with observations, interviews, and documentation. The results of the study indicated that: (1) Unlicensed mining activities in Katingan Regency cause environmental damage if left behind, environmental damage will become worse, from the problems of the government Formulating the people's mining area policy as a place for people working in the community. (2) With the policy of the mining area of people's mining problems without permits can be resolved and the environmental damage will be reduced while the proposed territory is certainly fast there is Potential. (3) The benefit of this policy is to increase the regional real income (PAD) of Katingan County. (4) The policy is still not able to be published until the decision of the Ministry of Energy and Mineral resources, but the territory has been proposed to the Government of Katingan Regency. (5) If this policy is still not established then the Government will make regional regulations or rules of the regent.